2014
DOI: 10.4238/2014.august.29.6
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopic imaging of brain injury after nasopharyngeal cancer radiation in early delayed reaction

Abstract: This study aimed to investigate the value of magnetic resonance spectroscopy (MRS) imaging in assessing nasopharyngeal carcinoma radiotherapy during the early delayed reaction period. Eighty cases of nasopharyngeal cancer treated with radiotherapy within the same period underwent MRS imaging before or after radiotherapy. Of the 80 cases, 47 underwent MRS imaging on the 3rd, 4th, 6th, and 12th months after radiotherapy. The trends of the primary metabolite concentration at different time points were monitored a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…This is the first‐reported fMRI‐based RT‐injury study. Several pioneering studies using other functional modalities—for example, PET, perfusion MRI, single‐photon emission computed tomography (SPECT), and MRS—have been conducted mainly to investigate RT‐induced necrosis [Chan et al, ; Chen et al, ; Chong et al, ; Kim et al, ; Matulewicz et al, ; Schwartz et al, ; Sundgren, ; Tsui et al, ] or other MR‐invisible lesions [Wang et al, ; Xiong et al, ]. These results can support our findings, as fMRI is also related to cerebral vascular function and perfusion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This is the first‐reported fMRI‐based RT‐injury study. Several pioneering studies using other functional modalities—for example, PET, perfusion MRI, single‐photon emission computed tomography (SPECT), and MRS—have been conducted mainly to investigate RT‐induced necrosis [Chan et al, ; Chen et al, ; Chong et al, ; Kim et al, ; Matulewicz et al, ; Schwartz et al, ; Sundgren, ; Tsui et al, ] or other MR‐invisible lesions [Wang et al, ; Xiong et al, ]. These results can support our findings, as fMRI is also related to cerebral vascular function and perfusion.…”
Section: Discussionsupporting
confidence: 84%
“…The above findings, however, were not consistent with those from the brain tumor studies, in which different white matter areas, such as the parahippocampal cingulum bundles [Chapman et al, ] and the genu and splenium of the corpus callosum [Nagesh et al, ] were assessed and revealed a gradual course towards abnormality, which again indicates progression of structural abnormalities. In addition to DTI, both our group [Wang et al, ; Xiong et al, ] and another group [Chen et al, ] have used magnetic resonance spectroscopy (MRS) to measure brain tissue metabolism and neuronal function in post‐RT, normal‐appearing nasopharyngeal carcinoma patients, but this modality is hampered by heavy noise and poor spatial resolution [Jansen et al, ], as well as the same ROI‐definition problem. More advanced brain functional study using functional magnetic resonance imaging (fMRI) has been largely neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Modern neuroimaging techniques, such as MRS and DTI, have provided fascinating insights into microscopic abnormalities in the normal appearing brain parenchyma in Post-RT. For instance, an MRS study (Chen et al, 2014) found dynamic and transient metabolic alterations in the temporal lobe. Using TBSS, one DTI study demonstrated dynamic and complex WM microstructural changes in the earlier phases of RT (Duan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Except for the brain structural abnormalities, [6] the radiation-induced functional deficits of NPC patients were also extensively investigated applying statistic analysis, such as performing the Montreal Cognitive Assessment (MoCA). Surveys have indicated that the NPC patients with RT (RT+) generally showed lower MoCA scores than the NPC patients without RT (RT−), demonstrating that RT would induce the cognitive deficits in NPC patients.…”
Section: Introductionmentioning
confidence: 99%